Leaf chlorosis in Arabidopsis thaliana hybrids is associated with transgenerational decline and imbalanced ribosome number. Issue 3 (15th July 2020) - Vaid, Neha; Ishihara, Hirofumi; Plötner, Björn; Sageman‐Furnas, Katelyn; Wiszniewski, Andrew; Laitinen, Roosa A. E.
Summary: The interaction of two parental genomes can result in negative outcomes in offspring, also known as hybrid incompatibility. We have previously reported a case in which two recessively interacting alleles result in hybrid chlorosis in Arabidopsis thaliana . A DEAD‐box RNA helicase 18 ( AtRH18 ) was identified to be necessary for chlorosis. In this study, we use a sophisticated genetic approach to investigate genes underlying hybrid chlorosis. Sequence comparisons, DNA methylation inhibitor drug treatment and segregation analysis were used to investigate the epigenetic regulation of hybrid chlorosis. Relative rRNA numbers were quantified using real‐time quantitative PCR. We confirmed the causality of AtRH18 and provided evidence for the involvement of the promoter region of AtRH18 in the hybrid chlorosis. Furthermore, AtMOM1 from the second parent was identified as the likely candidate gene on chromosome 1. Chlorotic hybrids displayed transgenerational decline in chlorosis, and DNA demethylation experiment restored chlorophyll levels in chlorotic hybrids. Quantification of rRNA indicated that hybrid chlorosis was associated with an imbalance in the ratio of cytosolic and plastid ribosomes. Our findings highlight that the epigenetic regulation of AtRH18 causes hybrid breakdown and provide novel information about the role of AtRH18 in plant development.